Pengujian Aktivitas Antibakteri Sabun Cair dari Ekstrak Kulit Daun Lidah Buaya - Sari, Rafika; Ferdinan, Ade (Pharmaceutical Sciences and Research, 2017)
Aloe vera is one of the typical plants found in Pontianak, West Kalimantan. This plant’s leaf peel is nontoxic and can be used as an antibacterial and anti-inflammatory agent. Nowadays, Aloe vera is one among 10 most popular plants in the world that have a potency to be developed as medicinal plant. This study aimed to determine antibacterial activity of the extract of Aloe vera leaf peel in liquid soap formulation against several pathogenic bacteria. Aloe vera leaf peel extract was prepared with maceration using ethanol. Then, it was formulated into a liquid soap. The soap was evaluated for its organoleptic, pH value, specific gravity, and foam height. Antibacterial activity assay of the liquid soap was carried out using diffusion method. The results showed that the characteristic of the liquid soap was viscous, yellowish white colored, and had distinctive smell of Aloe vera. The pH values on the day 0, 7 and 14 were 8; 8,9; and 9,4; respectively. The specific gravity was 1,033 g/ml. The foam height on minute 5, 10 and 15 were 76.92%, 19.23% and 19.23%, respectively. The liquid soap from the extract of Aloe vera leaf peel was found to have antibacterial activity against Gram positive bacteria (Staphylococcus aureus, Staphylococcus epidermidis, Bacillus subtilis, and Bacillus cereus) and Gram negative bacteria (Salmonella typhimurium, Proteus mirabilis, Pseudomonas aeruginosa, and Escherichia coli).